Effect of elimination diets on the functioning of children with autism in the opinion of parents - Sylwia Jaruga-Sękowska; Monika Mazur; Wiktoria Staśkiewicz; Joanna Woźniak-Holecka; Gabriela Wanat-Kańtoch (Kazimierz Wielki University, 2022)
Introduction.  The autism spectrum disorder is more and more common in the world and is diagnosed in the early years of childhood. This disorder is impossible to cure, so parents are increasingly looking for the best therapies for their children. The most popular are the use of elimination diets, including gluten-free and casein-free diet. Material and methods. The study was conducted on a group of 95 people: 68 women and 27 men. The Cole index was used to assess the nutritional status of children with ASD. Taking into account the interpretation, it can be concluded that almost half of children with ASD have a normal nutritional status.There are 65 children with ASD who  have complaints of impaired gastrointestinal function, the most common symptoms are gas, constipation, bloating and abdominal pain. Results.  The most common and popular of the alternative treatment support methods for a child with ASD used by parents are elimination diets. Among the most commonly used can be a diet that is either casein-free, gluten-free, sugar-free, or a diet with elimination of specific ingredients. In our study, we found that there is a significant relationship between the use of an appropriate nutritional strategy and improved digestive functioning in a child with ASD. Conclusions. Based on the results, it was concluded that there is a significant correlation between the use of a gluten-free diet and / or a non-dairy diet, and the improvement in the functioning of the digestive system, quality of life and behavior of children with autism. According to the subjective opinion of parents, a gluten-free and dairy-free diet improves the quality of life and behavior of a child with ASD.